Strengthening Religious Moderation as A Hidden Curriculum in Islamic Religious Universities in Indonesia - Ade Arip Ardiansyah; Mohamad Erihadiana (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article aims to offer an ingredient so that radical thinking in universities, especially in Islamic universities, is not contagious and systemically infected. The growth of radicalism in college based on surveys in recent years has increased. Through literature review and qualitative analysis, it was found that: a) in Apple's lens, the growth of radicalism in colleges stems from ideologies working in the built-in education system; b) religious moderation needs to be used as a shield or counters to the growth of the seeds of radicalism; c) the operationalization of religious moderation (tolerant and inclusive attitude) as a hidden curriculum can be done in three positions at once, namely hidden curriculum as an instrument, religious moderation as a hidden value and religious moderation as hidden curriculum planned in secret by lowering CPL to a more operational and measurable CPMK.